Pengaruh Organizational Justice Dan Religiosity Terhadap Employee Fraud Dengan Dimediasi Whistleblowing Intention - Erine Saskia Anggraini; Reskino Reskino (Akuntabilitas, 2020)
This study aims to examine the influence of organizational justice and religiosity on employee fraud mediated by whistleblowing intention. This study uses primary data by distributing questionnaires to employees who work in Islamic banks in the DKI Jakarta area. Sampling was done using the purposive sampling method. This study used sample of 71 respondents. The data analysis method that used as Partial Least Square (PLS)-SEM with the help of data analysis tool SmartPLS 3.0. The results of this study indicate that religiosity shows significant effect on whistleblowing intentions. Organizational justice unable to contribute significantly to whistleblowing intention. Whistleblowing intention have a significant effect on employee fraud. Organizational justice and religiosity unable to contribute significantly to the employee fraud. Furthermore, religiosity significantly influence on employee fraud through whistleblowing intentions. Organizational justice unable to contribute significantly to employee fraud through whistleblowing intentions